Metabolic Skeletal Superscan on 18F-FDG PET/CT in a Case of Acute Lymphoblastic Leukemia. (July 2015) - Parida, Girish Kumar; Soundararajan, Ramya; Passah, Averilicia; Bal, Chandrasekhar; Kumar, Rakesh
Abstract : Abstract: Superscan is a well-known finding described in skeletal scintigraphy characterized by intense radiotracer uptake in axial skeleton and decreased uptake in soft tissues and kidneys. Metabolic skeletal superscan has also been described in 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET)/computed tomography (CT) in various conditions. We describe here a case of 12-year-old boy who presented with a scalp swelling, progressive pallor, easy fatigability, poor appetite, and fever for 6 months. The initial diagnosis was inconclusive. 18 F-FDG PET/CT revealed metabolic skeletal superscan and the final histopathological diagnosis was acute lymphoblastic leukemia.